2019
DOI: 10.1108/jcm-05-2017-2199
|View full text |Cite
|
Sign up to set email alerts
|

The influence of corporate brand perceptions on consumer satisfaction and loyalty via controlled and uncontrolled communications: a multiple mediation analysis

Abstract: Purpose Drawing on the stimulus–organism–response (S-O-R) model, the purpose of this study is to investigate mediating effects of controlled and uncontrolled communications of corporate brand perceptions on consumer satisfaction and loyalty. Design/methodology/approach Structural equation modeling (SEM) was used to test the hypotheses on a sample of 271 Australian automobile consumers. Findings The authors find that while consumer satisfaction is indirectly influenced by corporate-level attributes via cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 133 publications
(173 reference statements)
1
21
0
Order By: Relevance
“…Sequential in nature, the S-O-R model explains how the stimuli cues from the external environment could fortify the internal state of individual and elicit their approach or avoidance behaviour (Arora, 1982;Eroglu et al, 2003). The prominent emergence of digitalization in the retail industry has further marked the extension of the S-O-R model into a different perspective to advance the understanding of consumers' reaction and their subsequent behaviour within different selling environment (Anisimova et al, 2019;Cheah et al, 2019;Liu et al, 2019).…”
Section: Stimulus-organism-response Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequential in nature, the S-O-R model explains how the stimuli cues from the external environment could fortify the internal state of individual and elicit their approach or avoidance behaviour (Arora, 1982;Eroglu et al, 2003). The prominent emergence of digitalization in the retail industry has further marked the extension of the S-O-R model into a different perspective to advance the understanding of consumers' reaction and their subsequent behaviour within different selling environment (Anisimova et al, 2019;Cheah et al, 2019;Liu et al, 2019).…”
Section: Stimulus-organism-response Modelmentioning
confidence: 99%
“…This research adopted a non-probability sampling method in which the target respondent was Gen-Z consumers. Likewise to past research (Anisimova et al, 2019;Choi and Kim, 2016), a pre-test with five Gen-Z consumers and five marketing academics was conducted to increase the understanding and clarity of the questionnaire prior actual distribution to respondents. After the comments from the pre-test sample, slight modifications regarding wording and grammar structure were made to the questionnaire to improve the clarity of the scale items.…”
Section: Sample and Data Collectionmentioning
confidence: 99%
“…The association between satisfaction and loyalty has gained increasing attention from marketing scholars (Lombart and Louis, 2012;Seiler et al, 2013;Anisimova et al, 2019;Lu et al, 2019). While customer satisfaction significantly influences loyalty (Orel and Kara, 2014;Casidy and Wymer, 2016;Meesala and Paul, 2018;Lai, 2019;Song et al, 2019), research has suggested that the consideration of potential mediating variables may better explain the nature of this relationship (Castañeda, 2011;Kumar et al, 2013;Schirmer et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Nguyen (2006) defines corporate image as what comes to the minds of customers when they hear the name of a company. Corporate image can play a vital role in both attracting and retaining customers (see also Anisimova et al, 2019). Research undertaken by Kandampully and Hsin-Hui (2007) to investigate the direct and indirect impact of corporate image on customer loyalty in the hospitality industry confirmed that corporate image has a favorable influence on customer loyalty.…”
Section: Customer Retentionmentioning
confidence: 95%